A educação física no Colégio Estadual do Espírito Santo : atores, práticas e representações (1943-1957) - Poleze, Grasiela Martins Lopes (2014)
The study is part of the research "History and Memory of Physical Education and sport in Espírito Santo: authors, actors and institutions (1931-1961)". It Seeks to understand the process of institutionalization of Physical Education as a school discipline in the Espírito Santo region between the 1940s and 1950s. It has the Physical Education as object of investigation in the Colégio Estadual do Espírito Santo, in order to realize some of their practices, their actors and their representations in capixaba society. As a theoretical and methodological framework, uses the concepts of strategy and tactics , representation struggles and evidentiary paradigm. The sources for the study are the files of the Colégio Estadual do Espírito Santo, the permanent archive of the Centro de Educação Física e Desportos from Universidade Federal do Espírito Santo, articles from Vida Capichaba magazine and newspapers A Gazeta and A Tribuna in sports sections, the Aloyr Queiroz Araújo archive (former teacher from the Colégio Estadual), as well as interviews with the actors who were part of the history of the institution investigated. The academic productions reveal a told history of the Colégio Estadual based on official documents and narrated from the antagonism between related desire of the capixaba society to modernize before the Brazil and the true structural conditions that institution in making this dream possible. On the focused period, the Physical Education shall become progressively more sportive and less related to the teaching of gymnastics, due to the appreciation of the Olympic movement in the early twentieth century, sports after World War II and also the economic changes in Brazil and in the State of Espírito Santo. Moves the focus of the Physical Education from orthopedics objectives to the search for effectiveness. Located on printed materials indicate the importance that the institution takes to the formation of capixaba elite, which also happens with reference to sports, since the achievements of the school, in sports field constantly appear in the journals analyzed. The presence of the college in the civic moments represented in the documents, highlights the patriotic feeling of youth, even with the incentive of state policy. The sport, in the studied context, indicates the effort of this society to highlight the progress made in the quest to overcome its political and economic conditions and as part of its project to engage in modernization of the country. Interviews showed some counterpoints between what is intended with the ideal designed for school and Physical Education and the real attitudes of some of his actors. The sport is named as a present and valued practice in school activities, mingling with practices held in the Physical Education classes.